Marine Vibrator Concepts for Modern Seismic Challenges. Issue 1 (1st December 2018) - Long, Andrew; Tenghamn, Rune
Abstract : Aside from historical issues of mechanical durability and efficiency, the design of marine vibrators (MVs) for towed streamer operations are confronted by several practical challenges to their different possible applications: 1. Alternatives to conventional air gun arrays for flexible and creative acquisition geometries, 2. Low power alternatives to air gun arrays for environmentally sensitive applications, and 3. High power ultra-low frequency sources specific to Full Waveform Inversion (FWI) optimization. One relevant consideration to MV operations is the volume of water that must be displaced per cycle to achieve a desired Sound Pressure Level (SPL); increasing exponentially as the frequency of interest decreases, and becoming significant at frequencies less than about 5 Hz. This is particularly relevant for FWI optimization as the frequencies of interest are in the range of 1-6 Hz. Another consideration is that ultra-low frequency output theoretically benefits from deeper towing enhanced by the well-known free-surface ghost effect, but in practice, deeper towing is confronted by an air spring effect that increases the force required per cycle to generate a desired SPL, and is due to the surrounding hydrostatic pressure at depth. Environmental motivations to develop low power vibrator concepts are driven by regulatory restrictions upon received SPL and Sound Exposure Level (SEL), and we demonstrate how low power MVs can be configured to yield low SPL and SEL metrics without compromising geophysical performance-in contrast to the use of air gun arrays with few elements. MVs enable independence from large compressors and may be more easily deployed in spatially distributed geometries than air gun arrays. We present examples of flextensional MV development verified by numerical modelling, tow tank testing, and field verification; collectively supporting the principles discussed herein.